Characteristics of Energy Distribution in a Desert Ecosystem in Inner Mongolia, Northern China - Pan, Yumeng; Xiao, Huijie; Xin, Zhiming; Li, Junran; Miri, Abbas; Cao, Qiqi (Frontiers in Environmental Science, 2022)
Desert ecosystems are vulnerable to climate change because of their fragile environment and poor self-regulation ability. Exploring the land–surface energy balance and the water/heat transfer processes of such regions for water resource management purposes is critical. The processes of surface water and heat transfer throughout the desert ecosystems and the effects of environmental factors on the energy distribution remain poorly studied. In this study, we used an eddy covariance system and surface meteorological data (2019–2021) to investigate the characteristics of the energy balance of Dengkou Desert ecosystem located in Inner Mongolia, northern China. Also, we evaluated the effects of different environmental factors on the energy distribution in this desert ecosystem. We found that the temporal patterns of both sensible heat flux (H) and latent heat flux (LE) with time are consistent with that of net radiation (Rn), and Rn is dominated by H. The sum of the daily average soil heat flux during the observation period was positive, indicating that soil was a heat sink and that the atmosphere transfers heat to the soil. During the observation period, the energy distribution of H/Rn fluctuated greatly, presenting a general U-shaped trend, while LE/Rn presented an inverted V-shaped trend. The main factor affecting H was Rn, followed by saturated vapor pressure, air temperature (Ta), and relative humidity. For LE, the main influencing factors were Ta, and Rn. The energy closure of the half-hour flux in the Inner Mongolian desert ecosystem during the observation period was 48%–68%, and the energy balance ratio was 0.54–0.74. The energy closure at the daily scale was higher than that at the half-hour scale, and the energy closure during daytime was higher than that at night.